Potencial agroproductivo de variedades de camote (ipomea batatas l.)para el valle del rio carrizal. - Loor Delgado, Jorge Javier (2015)
The present research work was fulfilled during the dry season in the experimental field of the conventional area of the ESPAM - MFL.The of this research was to determine the agroproductivity of three varieties of yam: Orange, Purple Ecuador, Guayaco Morado, under the conditions of soil and weather of the valley of the river CARRIZAL. For the statistical analysis of the variables they were submitted to the checking average of tukey. And the economic analysis was established by the CIMMYT, the variables, weight of tubers was analyzed statistically by plants (kg), number of tubers / plants, guides' length (cm), diameter of tubers (cm), length of tubers (cm) and numbers of guides / plants, these to the being evaluated statistically appeared significant differences. The treatments that show to be more favorable for the variable in study was treatment 3, variety purple Guayaco, that gave the best rate of marginal return that, for every reversed dollar obtains profitability of 0, 23 dollar.